If You Build It, Will They Come? Predictors of Teachers’ Participation in and Satisfaction with the Effective Classroom Interactions Online Courses - LoCasale-Crouch, Jennifer; Hamre, Bridget; Roberts, Amy; Neesen, Kathy (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
The Effective Classroom Interactions (ECI) online courses were designed to provide an engaging, effective and scalable approach to enhancing early childhood teachers’ use of classroom practices that impact children’s school readiness. The created courses included several versions aimed at testing whether or not certain design aspects could increase participation and subsequent learning outcomes. The purpose of this study was to examine the extent to which early childhood teachers accessed the courses and varied in their a) participation in the core course content and b) optional discussion board as a result of the course experience they were assigned to as well as individual characteristics that may be associated with participation. Findings indicated that early childhood teachers accessed the course often on nights and weekends and reported high levels of satisfaction with their experience. Both persistence in the ECI courses and overall completion of activities were higher than those reported in other studies of online learning. Whether or not the participant was in the course that had regular interactions with the instructor, comfort with technology and took the course for credit consistently predicted participation, but not always in expected ways. Implications for exploring online learning as a feasible option for early childhood educators are discussed.